The Effect of Financial literacy and Attitudes on Financial management behavior through Community behavioral intentions - denytasari, Rizma; Khoiriawati, Novi (Enrichment : Journal of Management, 2023)
This study aims to examine the direct and indirect effects of financial literacy and financial attitudes on community financial management behavior through behavioral intention as a mediating variable. The population in this study were the people of Boyolangu District totaling 85,840 people using probability sampling techniques and determining the sample using the cluster sampling method using the Slovin formula so that 100 respondents were selected. This data analysis technique was carried out using the path analysis method using the SmartPLS application. The results of this study indicate that financial literacy has no effect on behavioral intention, financial attitudes have a positive and significant effect on behavioral intention, financial literacy and financial attitudes have a positive and significant effect on financial management behavior, behavioral intention does not mediate the effect of financial literacy on financial management behavior, behavioral intention mediates the effect of financial attitudes on financial management behavior, behavioral intention has a positive and significant effect on financial management behavior. The implication is that in managing finances, strong behavioral intentions are also needed so that individuals can manage their finances more effectively and wisely